(untitled) (Ustozlar uchun, 2024)
Currently, all the countries of the world, even though they are developed, are taking various measures to prevent internal poverty. This does not normalize the standard of living of the population, no matter how stable the economy is. On the contrary, large sums of money lead to formation in the hands of only one stratum. According to the World Bank, about 9.2% of the world's population (more than 700 million people) suffer from poverty, and in Central Asia this figure is equal to 40%. [1] [1] www.worldbank.com - The official website of World Bank